Analisis Pengaruh Tegangan dan Hambatan Terhadap Kuat Arus dengan Menggunkan Phet Simulation - hilma; Malik, Adam (JFT : Jurnal Fisika dan Terapannya, 2023)
In an increasingly modern era, increasingly advanced technology makes it very easy for the world of education, one of which is when carrying out practicum activities. so that practicum activities can be more flexible and can avoid work accidents. Practicum experiments, of course, vary, including resistors and incandescent lamps. The practicum aims to analyze the effect of voltage and resistance on the amount of current generated. The method used in this practicum is a quantitative method by conducting experiments or experiments with the Phet Simulation virtual lab. The results obtained from this practicum, the effect of voltage on current strength, the current strength will be greater when the voltage is increased, which means that the relationship between the two is directly proportional. While the influence of resistance, the greater the resistance given, the smaller the resulting current will be. This means that the relationship between resistance and current strength is inversely proportional.